DOES THE THEORY OF UNCOVERED INTEREST RATE PARITY HOLD FOR SRI LANKA - Nirmali, H.; Rajapakse, R.P.C.R. (EPRA Journals All Rights Reserved., 2017)
Attached

Interest rates and exchange rates are considered to be one cj the most discussed areas under International Finance. When considerinq the main theories that explore on these. two variables, Uncovered Interest Rate Parity (VIP) states that the interest rate differential is an unbiased predictor cj the spot exchanqe rate chanqes. The impact on investors' attitude is that they would be indifferent towards the returns on domestic and Joreian assets denominated in same currency thereb)f eliminating any short term arbitraae prifits. Studies based on the relationship between these two variables are rare Jor developinq countries like Sri Lanka. Therifore in order to bridae that aap identified throuqh search Jor literature, this study is Jocused on testina VIP Jor Sri Lanka. Autoreqressive Distributed Laps method was employed to test the VIP. Monthly data on exchanqe rates and three month risk free interest rates with reaard to the sel~cted major erternal trader, VSA Jor the period Jrom 2001-2014 were used Jor this purpose. The findinas reveal that there. is no evidence to prove the existence <1 VIP either in the lona run or in the short run Jor the VS$ compared aaainst . to the Sri Lankan Rupee.
Keywords: Interest Rates, . Exchange Rates, Uncovered Interest Rate Parity (UIP), Unit root tests, Autoressive Distributed Lags (ARDL) Model.